Addressing substance misuse in adolescents: a review of the literature on the screening, brief intervention, and referral to treatment model. Issue 2 (April 2016) - Beaton, Aimee; Shubkin, Catherine D.; Chapman, Steven
Abstract : Purpose of review: Adolescent substance use is a major public health concern in the United States. Pediatricians are in a unique position via the medical home to address this issue. Screening, brief intervention, and referral to treatment (SBIRT) is a comprehensive approach that aims to prevent, identify, and reduce substance use. SBIRT has been heavily studied in adults, but research with adolescents is still ongoing. This review examines the SBIRT model and highlights recent applicable research. Recent findings: This research indicates that alcohol and drug use has a negative impact on the developing brain. In 2011, the American Academy of Pediatrics (AAP) released a policy statement recommending the use of SBIRT. An adolescent SBIRT algorithm can be used clinically. Recent studies focus on individual components of SBIRT; however, there have been no studies that examine all three components together in adolescents. Nevertheless, research indicates that SBIRT is an important tool to assess and intervene regarding adolescent substance use. Summary: SBIRT is recommended by the AAP as a way to address adolescent substance use. Pediatricians should be screening adolescents for substance use at every well exam, and acute care visits when possible, with a validated tool. Although more research is needed, SBIRT is an effective method to address adolescent substance use.